Metrological characterization of standards – plastic films, which are used for calibration of nano volume spectrophotometers - Zarubica Veljko; Kubičela Edvard; Zarkov Boban; Srećković Milesa (EPJ Web of Conferences)
UV-VIS spectrophotometers, including nano drop (volume) spectrophotometers, provide an answer to all challenges in scientific and industrial laboratories, whether for pharmaceutical, chemical or service laboratories, all the way to more complex applications such as quantification of DNA, RNA, and protein per second, using only 1-2 μL of the sample. Certified reference materials are used to check the measurement capabilities of nanodrop spectrophotometers and other analytical instruments. Since these are solutions, which by themselves are not practical in terms of handling, stability, availability, we were thinking of using materials for their calibration, which would have more suitable properties than the solutions. We decided to use plastic films, which are thin enough not to be a problem during manipulation and measurement, which are stable in terms of determining the regular absorbance, which are optically neutral in the wider spectrum of optical radiation, and which are temperature stable and do not change their metrological characteristics during prolonged exposure to light. The paper evaluates all these influential characteristics and presents the budget of measurement uncertainty of plastic films in the UV part of the optical radiation spectrum at wavelengths of 260 nm and 280 nm (Fig.6). The term “metrologically characterized materials” represent equivalent of the materials, with precisely define regular absorbance (e.g., absorption), as well as estimated influential parameters which may appear, thus contributing to the uncertainty of the measurement.